THU0301 A Phase II Trial of Retinoids on Lupus Nephritis in A Single Center. (15th July 2016) - Funauchi, M.; Nozaki, Y.; Kinoshita, K.
Abstract : Background: Although immunosuppressants such as corticosteroids or cyclophosphamide can suppress the progression of LN, a major manifestation of systemic lupus erythematosus (SLE), some cases are resistant to those agents, and severe adverse reactions (ARs) may occur. Therefore, development of new effective drugs with fewer ARs is important. Recently, all-trans retinoic acid (ATRA), one of natural retinoids, has been reported to differentiate regulatory T cells and suppress Th17 cells in the models of autoimmune diseases. We have reported that ATRA improved proteinuria, survival rate as well as renal pathology in lupus-prone mice (ref). On the other hand, AM80, a synthetic retinoid, has been reported to suppress the expression of inflammatory cytokines in collagen-induced arthritis and EAE. Objectives: Effectiveness and safety of these retinoids for the treatment of LN were examined. Methods: Twenty-three patients with LN who fulfilled the ACR's revised criteria for classification of SLE were enrolled. Those unable to prevent pregnancy for more than 2 years, and who had been newly given any immunosuppressants within 8 weeks before this study were excluded. ATRA (10 mg/day) was administered to 9 patients (group A) and AM80 (4 mg/day) to 14 (group B) for 6M. Six in group B dropped out due to ARs, and effectiveness was analyzed using data of 8 patients. Through the study, the dose of steroid was not increased but allowed to be reduced if the clinical course was improved. Urinary protein (UP), serum albumin (Alb) and creatinine (Cr) levels, titer of the serum anti-double-strand DNA antibody (ADNA), serum complement levels (C3, C4) and activity (CH50) were determined every month. Results: In group A, Average of UP decreased at 6M after the treatment (3.2 to 0.4 g/g Cr, p<0.05), Alb tended to elevate (3.2 to 3.8 g/dl), and Cr did not change. ADNA tended to reduce from 23.5 to 15.5 IU/ml, and C3, C4 and CH50 tended to elevate. In group B, UP tended to reduce at 6M (2.3 to 1.3), while Alb and Cr did not change. ADNA reduced from 37.6 to 18.8 at 3M and kept the similar value at 6M. Serum C3, C4 and CH50 tended to elevate until 6M. In group A, ARs occurred in 3 cases (leucopenia, fatigue and myalgia), while skin rash occurred in 4, bone pain in 3, hair loss in 3, and faintness, hypertension and fever in one case each in group B. AM80 was discontinued in 6 cases due to bone pain, faintness, hypertension and fever within 2M. Dose of steroid tended to reduce at 6M (A:17.1 to 15.0, B:13.6 to 13.2 mg/day). Conclusions: This is the first report of on effectiveness and safety of retinoids for LN. Although the difference did not reach significance due to lack of number, UP and ADNA tended to reduce, Alb elevate, and complements tended to elevate in the both groups. Dose of steroid was reduced in some cases. Number of the cases was not enough mainly because of the exclusion criteria of contraception. Bone pain occurred relatively frequently and caused dropout in AM80 group, although it was not so severe. These findings suggest that retinoids might have a role in improvement of LN resistant to conventional therapy, and ancillary role of retinoids to high-dose steroids or immunosuppressants should be also tested in future. References: Kinoshita K, Funauchi M, et al.: Retinoic acid reduces autoimmune renal injury and increases survival in NZB/W F1 mice. J Immunol. 170:5793, 2003. Disclosure of Interest: None declared